ANALYSIS OF THE USE OF AKAD KAFALAH BI 'UJRAH ON BSI HASANAH CARD PRODUCTS AT BSI BANK – KCP UINSA SURABAYA - Filla Apriliani Mahfudloh; Syahrul Asy’ari, Mochammad (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2023)
This research aims to find out how the kafalah contract is used in BSI Hasanah Card products. The research method used is a qualitative method using a descriptive approach. The data sources used are primary data and secondary data. Primary data was obtained through a direct interview process with BSI KCP UINSA Surabaya. Secondary data was obtained from various literary sources such as books, journals, articles and other documents that support discussions related to the research theme. The results of this research show that the BSI Hasanah Card is in accordance with sharia principles. BSI Hasanah Card uses three sharia contracts, namely the kafalah bil ujrah, qard and ijarah contracts. The use of the BSI Hasanah Card places restrictions on its users by not being able to use it for types of transactions that are not in accordance with sharia. This can provide a sense of security and eliminate worry for BSI Hasanah Card users from all forms of transactions that contain elements of gharar and usury and are not in accordance with sharia provisions.